Perancangan Insinerator Ramah Lingkungan Penghasil Arang dan Asap Cair - Suci Ramadhani; Dana Aswara; Emon Azriadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to design an incinerator using the Pahl and Beitz method so that people can get comfort and convenience in burning environmentally friendly waste and can also increase people's economic income in utilizing charcoal and liquid smoke, developing a simple incinerator design into an environmentally friendly incinerator that is environmentally friendly. can produce charcoal and liquid smoke. The benefits for researchers are increasing knowledge for researchers about product design and being able to apply the knowledge gained during lectures to real aspects, and for the University as a library treasury, which can provide benefits for students who conduct research with the same problem and become the subject of more research. continue in the future. The type of research used in this research is survey research by utilizing incinerators to produce charcoal and liquid smoke. From the research conducted, it is concluded that the results of the design of an environmentally friendly incinerator that produces charcoal and liquid smoke are designed according to the plan, the construction of this waste burner is made of drum material which has a diameter specification of 0.58 M high 0.89 M with a capacity of 200 liters. Garbage that is burned is solid waste. It is hoped that this incinerator can be used as a means to reduce landfill waste and can be used as a medium for managing household waste for the community in the Bangkinang sub-district of the city.